2014
DOI: 10.1124/dmd.114.060285
|View full text |Cite
|
Sign up to set email alerts
|

Gene Variants in CYP2C19 Are Associated with Altered In Vivo Bupropion Pharmacokinetics but Not Bupropion-Assisted Smoking Cessation Outcomes

Abstract: Bupropion is used clinically to treat depression and to promote smoking cessation. It is metabolized by CYP2B6 to its active metabolite hydroxybupropion, yet alterations in CYP2B6 activity have little impact on bupropion plasma levels. Furthermore, less than 10% of a bupropion dose is excreted as urinary bupropion and its characterized metabolites hydroxybupropion, threohydrobupropion, and erythrohydrobupropion, suggesting that alternative metabolic pathways may exist. In vitro data suggested CYP2C19 could met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 30 publications
3
29
2
Order By: Relevance
“…These results are consistent with the effect of CYP2C19 polymorphism on TB and EB in nonpregnant subjects (Zhu et al, 2014). However, it appears that CYP2C19 metabolizer phenotype did not influence the levels of BUP and, consequently, its AUC ss and Cl/F ss in pregnant subjects in our study.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…These results are consistent with the effect of CYP2C19 polymorphism on TB and EB in nonpregnant subjects (Zhu et al, 2014). However, it appears that CYP2C19 metabolizer phenotype did not influence the levels of BUP and, consequently, its AUC ss and Cl/F ss in pregnant subjects in our study.…”
Section: Discussionsupporting
confidence: 82%
“…These data suggest an increase in the reductive metabolism of BUP in pregnancy. However, CYP2C19 also contributes to the hydroxylation of BUP and its metabolites, TB and EB (Chen et al, 2010;Zhu et al, 2014). We observed that, relative to late pregnancy, the AUC ss of EB was higher in mid-pregnancy, suggesting a decreased rate of EB metabolism in mid-pregnancy, possibly due to pregnancy-induced downregulation of CYP2C19 (McGready et al, 2003).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…2A). Notably, whereas CYP2B enzymes play a major role in bupropion hydroxylation, other P450 enzymes, including CYP2C and CYP2E1, have been found to have low activity levels toward bupropion (Faucette et al, 2000;Chen et al, 2010;Pekthong et al, 2012;Zhu et al, 2014). However, the induction and sex difference of these non-CYP2B6 activities do not account for the sex difference in bupropion hydroxylase activities seen in the CYP2B6-humanized mice ( Fig.…”
Section: Discussionmentioning
confidence: 81%